The Arch of Sergi in Pula: an antique model for Renaissance originals - Gudelj, Jasenka (2007)
The Arch of Sergi in Pula, a town in Istria, is an honorary arch whose architectural disposition encountered particular critical fortune from the Renaissance times. The somewhat liminal position of Pula on the east Adriatic coast, its decadence from the 16th century and the lack of historical information and research on the urban history, contributed to form an atmosphere of Pula as a “ non – place” , eliminating the strata of cultural references for the antique monuments present in town. The first part of the paper explores these references and their dissemination and tries to reconnect the antique monument to its urban context. The second part of the paper explores the translation of its architectural form into different media, i. e. architectural drawing. Some 20 different two dimensional representations are known, and it is particularly interesting to discuss the problem of the original and the copy related to the practice of the drawing and measuring of the monument, producing first the imprecise working drawing which is normally copied in order to transform it into a more legible form and then copied again by other artists. The dissemination of the architectural drawings of the Arch of Sergi is particularly fortunate for the discussion, given its geographical position and examples covering whole range of representations possibly classified as copies, copies from the lost original (drawing), drawings published in printed architectural treatises. The Arch of Sergi inspired important works of art such as the Arsenale gate in Venice, the Aragonese Arch in Naples, the drawings of Jacopo Bellini and the paintings of Andrea Mantegna. Each of these works of art establishes a separate net of cultural connotations regarding the “ original” or the “ prototype” , its reception and oscillation of denotation, even esthetic valorization. Although the paper concentrates on only one antique monument, the analysis of its critical fortune though fifteen and sixteen centuries opens much broader discussion on the binomes original/copy and prototype/example.
Projekt MZOS
ENG